2018
DOI: 10.1159/000489744
|View full text |Cite
|
Sign up to set email alerts
|

Serum from Chronic Hepatitis B Patients Promotes Growth and Proliferation via the IGF-II/IGF-IR/MEK/ERK Signaling Pathway in Hepatocellular Carcinoma Cells

Abstract: Background/Aims: Chronic hepatitis B virus (HBV) infection (CHB) plays a central role in the etiology of hepatocellular carcinoma (HCC). Emerging evidence implicates insulin-like growth factor (IGF)-II as a major risk factor for the growth and development of HCC. However, the relationship between HBV infection and IGF-II functions remains to be elucidated. Methods: Levels of circulating IGF-II and IGF-I receptor (IGF-IR) in healthy donors (HDs) and CHB patients were tested by ELISA. Human HCC cell lines (HepG-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 40 publications
0
16
0
Order By: Relevance
“…For VEGF, the concentration that we used in the serum-free experiments (25 ng/mL) was similar to the concentration in medium supplemented with 20% human serum (22-45 ng/mL) [50][51][52]. However, the concentrations of IGF2 and IGFBP3 were relatively low in our experimental setup as compared to medium supplemented with 20% serum and especially that of IGFBP3 [24,[53][54][55]. A comparison of these concentrations can only be performed with caution because of the interactions between these proteins and other IGF family members [11].…”
Section: Discussionmentioning
confidence: 68%
“…For VEGF, the concentration that we used in the serum-free experiments (25 ng/mL) was similar to the concentration in medium supplemented with 20% human serum (22-45 ng/mL) [50][51][52]. However, the concentrations of IGF2 and IGFBP3 were relatively low in our experimental setup as compared to medium supplemented with 20% serum and especially that of IGFBP3 [24,[53][54][55]. A comparison of these concentrations can only be performed with caution because of the interactions between these proteins and other IGF family members [11].…”
Section: Discussionmentioning
confidence: 68%
“…Many findings implicate HBV infection as a major risk factor in the development of HCC [33,35]. Here, we demonstrated that prolonged HBV infection in susceptible host cell line (HepG2-NTCP) or in long-term infected mice can suppress the expression of anti-tumor HNF4α, particularly at later time points.…”
Section: Discussionmentioning
confidence: 73%
“…Moreover, the effect of other cell signaling pathways, including ERK on HBV-mediated HNF4α suppression, have not been explored. Previous studies reported that serum from CHB patients enhanced cell growth and proliferation in HCC cells via the IGF-II/IGF-IR/MEK/ERK signaling pathway [33]. Moreover, HBx, through the activation of the ERK and p38 MAPK signaling pathways, promoted the metastasis of liver cancer [34].…”
Section: Discussionmentioning
confidence: 94%
“…Moreover, the effect of other cell signaling pathways including ERK on HBVmediated HNF4α suppression have not been explored. Previous studies reported that serum from CHB patients enhanced cell growth and proliferation in HCC cells via the IGF-II/IGF-IR/MEK/ERK signaling pathway [33]. Moreover, HBx through the activation of ERK and p38 MAPK signaling pathways promoted metastasis of liver cancer [34].…”
Section: Discussionmentioning
confidence: 94%